2007
DOI: 10.4049/jimmunol.179.9.5778
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-4 Mediates the Coinhibitory Function of DC-HIL on T Cell Activation

Abstract: Receptor-ligand interactions between APCs and T cells determine whether stimulation of the latter leads to activation or inhibition. Previously, we showed that dendritic cell-associated heparin sulfate proteoglycan-dependent integrin ligand (DC-HIL) on APC can inhibit T cell activation by binding an unknown ligand expressed on activated T cells. Because DC-HIL binds heparin/heparan sulfate and heparin blocks the inhibitory function of DC-HIL, we hypothesized that a heparin/heparan sulfate proteoglycan on activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 44 publications
(36 reference statements)
5
103
0
Order By: Relevance
“…We also found DC-HIL to deliver a potent inhibitory signal to T cells, in an Ag-independent manner, by binding a heparin/heparan-like saccharide of syndecan-4 (SD-4) on activated T cells (19,20). These findings led us to hypothesize that DC-HIL binds microbial pathogens in a similar manner.…”
Section: /Cd8mentioning
confidence: 73%
See 2 more Smart Citations
“…We also found DC-HIL to deliver a potent inhibitory signal to T cells, in an Ag-independent manner, by binding a heparin/heparan-like saccharide of syndecan-4 (SD-4) on activated T cells (19,20). These findings led us to hypothesize that DC-HIL binds microbial pathogens in a similar manner.…”
Section: /Cd8mentioning
confidence: 73%
“…Similarly, we showed DC-HIL to bind a heparin/ heparan sulfate (HS)-like saccharide of SD-4 on activated T cells (20). We thus posited that DC-HIL may also recognize microbial pathogens through a similar sugar moiety.…”
Section: Dc-hil Binds To Dermatophyte Cell Wallmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, this might also indicate a role of SDC4 for the function of other cell types. Indeed, activation-dependent upregulation of SDC4 was found in both, DCs and T cells 6,8 . It has been shown that depletion of SDC4 þ T cells suppressed CHS, an activated T-cell-driven disease 4 .…”
Section: Discussionmentioning
confidence: 98%
“…SDCs are transmembrane heparan sulfate proteoglycans interacting with growth factors and cytokines and a variety of extracellular matrix molecules via their heparan sulfate chains 5 . While SDC4 is ubiquitously expressed at low levels, an activation-dependent upregulation of SDC4 has been reported for macrophages, DCs and CD4 þ T cells [6][7][8] . SDC4 expression is often involved in migration and adhesion of various cells including DCs [9][10][11] .…”
mentioning
confidence: 99%